SUSTAINABLE DEVELOPMENT AND IMPACT OF GLOBALIZATION ON TRIBAL AGRICULTURAL ENVIRONMENT OF EAST SINGHBHUM DISTRICT IN JHARKHAND - Mahali, Dr. Samu (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2017)
Agricultural environment of tribes have own tradition and characteristics. They have own genetically land ownership, sheds, pesticides, fertilizer, agricultural processes, agricultural instruments, agricultural byproducts and irrigation etc. Population growth and impact of globalization have changed the whole agriculture system of tribes during 1951-2011. Byproduct of farmer like indigenous fishes, herbs, sheds (paddy),fertilizer are eroded and whole agricultural land of this TD Blocks are converted as unfertile and fellow land due to miss use of chemical pesticide and fertilizer. Marginal farmers have sold their bullock cart, bullocks and their landed property. Above genus agricultural and land use system before the development of industry in the study area: FOREST  / CULTIVATED LAND  SETTLEMENT AREA  CULTURAL ACTIVITIES AREA  RELIGIOUS LAND (Parle, 1992, p-408) CULTURAL ACTIVITIES AREA  RELIGIOUS LAND URBAN AREA (Parle, 1992, p408 Above genus land use and agricultural system after the development of industry or impact of globalization in the study area: FOREST MINES / CULTIVATED LAND  INDUSTRIAL AREA  SETTLEMENT AREA  Process of rapid population growth started from the establishment of Tata Iron and Steel Company in 1907 as well as copper mines at Mosaboni and Ghatshila in 1927. This development changed the land use and agriculture system of tribes. Though their Living standard, Educational and Economic condition had changed, they stand developed in all aspects but as a trade-off lost their socio-cultural composition land use a great deal. They must continue their positive traditional cultures and social traits and may do away with the negative sides like less